Power Relations In ‘Spider-Man: Across The Spider-Verse’ Movie (2023): A Foucauldian Analysis - Zulkarnaen, Dicky Morgana; Jauwena, Gavriel Dylan; Brasco, Putra Pratama Immanuel; Steinlie, Granardo (Jurnal Pendidikan Makarios, 2024)
This study aims at unveiling the power issue found in the movie, “Spider-Man: Across The Spider-Verse,” a multi-layered story and profound symbolism. This study analyzed the movie’s thematic effects using a variety of literary theories and cinematic analysis. Furthermore, the study investigated how the film's nuanced use of images and visual themes enhanced the overall story and elicits emotional resonance in the spectator. Having the movie analyzed, the theory of Power, Discipline and Punish: The Birth of the Prison by Mitchel Foucault (1977), was used to criticize the power dynamic issue in the movie. As a result, 1) Leadership Conflict and Sovereign Power: The clash between Miles and Miguel highlights a conflict in ideals within the spider society. Miguel, as a leader, exerts sovereign power to control events, showcasing the dynamic of leadership struggles. 2) Resistance Against Anomaly and Exclusion: The designation of Miles as an "anomaly" reveals the resistance within the spider-society against individuals who deviate from established norms. The effort to exclude anomalies reflects a form of resistance against those perceived as outliers. 3) Power Relations in Identity Discourses: The discourses shaping Miles' identity, such as the "spider-society discourse" and "family discourse," contributes to shaping the dynamic power relations; Miles' resistance to these discourses illustrates a struggle for individual recognition and acceptance. This analysis underlines the movie’s broader societal relevance and potential impact by studying the socio-cultural milieu in which it was produced.